2019
DOI: 10.3892/mmr.2019.10587
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑451 relieves inflammation in cerebral ischemia‑reperfusion via the Toll‑like receptor 4/MyD88/NF‑κB signaling pathway

Abstract: The present study was designed to investigate the role of microRNA-451 (miRNA-451) on cerebral ischemia-reperfusion and to explore its possible mechanism. The expression of miRNA-451 was downregulated in rats with cerebral ischemia-reperfusion. In an in vitro model of cerebral ischemia-reperfusion, the downregulation of miRNA-451 increased inflammation, demonstrated by increased levels of tumor necrosis factor α, interleukin (IL)-1b, IL-6 and IL-18. However, the upregulation of miRNA-451 expression decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…As a result of the activation of the aforementioned receptors, the transcription factor NF-kB (nuclear factor kappa B) triggers the expression of genes encoding pro-inflammatory molecules, including IL-1b (interleukin-1b), IL-6, IL-8 (interleukin 8), IL-18 (interleukin 18), and TNF-a. Another activated transcription factor involved in the expression of pro-inflammatory genes is AP-1 (activator protein 1), an important activator of IL-1 and TNF-a expression and the promotion of the expression of some adhesion molecules (50)(51)(52). The path from TLR4 receptors to NF-kB and AP-1 activation is mainly through the MyD88 protein (myeloid differentiation primary response protein) (53,54).…”
Section: General Viewmentioning
confidence: 99%
“…As a result of the activation of the aforementioned receptors, the transcription factor NF-kB (nuclear factor kappa B) triggers the expression of genes encoding pro-inflammatory molecules, including IL-1b (interleukin-1b), IL-6, IL-8 (interleukin 8), IL-18 (interleukin 18), and TNF-a. Another activated transcription factor involved in the expression of pro-inflammatory genes is AP-1 (activator protein 1), an important activator of IL-1 and TNF-a expression and the promotion of the expression of some adhesion molecules (50)(51)(52). The path from TLR4 receptors to NF-kB and AP-1 activation is mainly through the MyD88 protein (myeloid differentiation primary response protein) (53,54).…”
Section: General Viewmentioning
confidence: 99%
“… 62 This miRNA inhibits NF‐κB activity and consequently downregulates pro‐inflammatory molecules in several tissues. 63 , 64 , 65 Here, we observed a downregulation of miR‐451 in the MHC‐I heterozygous incompatible pregnancies, which suggests this microRNA is involved in the development of a pro‐inflammatory environment at the fetal–maternal interface. No other hypoxia‐specific miRNAs are among the differentially regulated miRNAs found in this study, suggesting the downregulation of miR‐451 is not due to hypoxia, but rather to other mechanisms.…”
Section: Discussionmentioning
confidence: 55%
“…Evidence suggested that NF-κB and MAPK pathways are typical pro-inflammatory signaling pathways involved in inflammation and lipid accumulation [ 23 , 24 ]. In addition, TLR4 activation can bind to the TLR structural domain of MyD88 and trigger a series of phosphorylation reactions to activate NF-κB kinase, thereby activating NF-κB [ 25 , 26 , 27 ] and ultimately promoting the production of TNF-α, IL-6, and IL-β [ 28 , 29 , 30 ]. Based on these studies, we investigated the expression of key proteins in the NF-κB and MAPK pathways in ox-LDL-induced foam cells.…”
Section: Resultsmentioning
confidence: 99%